2018
DOI: 10.4103/jcis.jcis_34_18
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Use of Radiation-Protective Apron among Interventionists in Radiology

Abstract: Objective:Radiation-protective aprons are commonly used by interventionists to protect against the harmful effects of ionizing radiation. Choice of appropriate aprons with respect to lead equivalence and weight is necessary for effective protection and reduced physical strain. This study evaluates the knowledge and practice of using radiation-protective aprons by interventionists.Materials and Methods:Ninety-one interventional radiologists who attended an annual interventional conference were provided with a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 11 publications
4
16
0
1
Order By: Relevance
“…Their study showed a greater incidence of cervical, rather than lumbar, problems. It was also noted that interventional cardiologists use aprons for longer periods, which increases the impact on the axial skeleton [12]. However, our study produced results similar to Moore.…”
Section: Discussionsupporting
confidence: 69%
“…Their study showed a greater incidence of cervical, rather than lumbar, problems. It was also noted that interventional cardiologists use aprons for longer periods, which increases the impact on the axial skeleton [12]. However, our study produced results similar to Moore.…”
Section: Discussionsupporting
confidence: 69%
“…As shown in the flow diagram reported in Figure 1 , a total of 2337 articles were retrieved. Of these, twelve studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] were finally included. All studies had a cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
“…In this same study, the number of years performing invasive procedures post-fellowship was found to be significantly related to having spine disorders: 26% of physicians with less than five years of experience reported spinal problems, while this percentage increased to 60% in those physicians who had more than 21 years of interventional practice. No specific relationship between the rate of orthopaedic injuries and yearly caseload was identified [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in physician preferences can be identified if desired and their use in an interventional x-ray facility having Cine or DSA can be standardized. 9,10 Hanging tableside drapes are shown to reduce the exposure by more than 90% via measurement. It is an important pre-procedure preparation that x-ray technologists attach the hanging drapes as standard room preparation.…”
Section: F | Effectiveness Of Personal Protective Equipmentmentioning
confidence: 99%